2015
DOI: 10.1186/s12858-015-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor directly interacts with Rac1-GTPase in the brain mitochondria

Abstract: BackgroundSmall Rho-GTPases are critical mediators of neuronal plasticity and are involved in the pathogenesis of several psychiatric and neurological disorders. Rac-GTPase forms a multiprotein complex with upstream and downstream regulators that are essential for the spatiotemporal transmission of Rac signaling. The sigma-1 receptor (Sig1R) is a ligand-regulated membrane protein chaperone, and multiprotein complex assembly is essential to sigma-receptor function.ResultsUsing immunoprecipitation techniques, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 34 publications
(50 reference statements)
1
45
0
Order By: Relevance
“…Recently, Natsvlishvili et al . [51] reported that, by using immunoprecipitation, the Sig-1R not only directly interacts with Rac1-GTPase, but also forms complexes with IP3R, BiP, and Bcl2, in the brain mitochondria. Interestingly, the ligand-specific assembly complex relies on the Sig-1R agonist/antagonist and the presence of GTP/GDP.…”
Section: Sig-1r–interacting Proteins Per Experimental Demonstrations mentioning
confidence: 99%
“…Recently, Natsvlishvili et al . [51] reported that, by using immunoprecipitation, the Sig-1R not only directly interacts with Rac1-GTPase, but also forms complexes with IP3R, BiP, and Bcl2, in the brain mitochondria. Interestingly, the ligand-specific assembly complex relies on the Sig-1R agonist/antagonist and the presence of GTP/GDP.…”
Section: Sig-1r–interacting Proteins Per Experimental Demonstrations mentioning
confidence: 99%
“…Navarro et al (2010) have also been reported. The S1R directly and indirectly modulates neuronal mitochondrial Rac-1 GTPase (Tsai et al, 2009;Natsvlishvili et al, 2015), which is involved in dendritic spine formation. S1R reduces tau phosphorylation (Tsai et al, 2015) via indirect regulation of cyclin-dependent kinase 5 (cdk5) and thus protects neuronal axon elongation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anti-oxidative stress function was abolished when Sig1-R was knocked out (Pal et al 2012). Sig1-R can also regulate the production of ROS through the ER-mitochondrial Rac1 system, and this system could promote a mild pro-oxidant milieu for cellular signaling and induce plastic transformation in neurons (Natsvlishvili et al 2015). 4-Phenyl-1-(4-phenylbutyl) piperidine (PPBP), a Sig1-R agonist, could protect neurons via a mechanism that involves the antiapoptotic protein Bcl-2 (Yang et al 2007).…”
Section: Sig1-rmentioning
confidence: 99%